The Implementation of the 2013 Curriculum in Arabic Learning Based on a Scientific Approach - Baiq Kurnia Buana; Adelia Dwi Karenina; Umi Nafiah; Wahyu Nurrohman; M. Nur Pahlevi (Universitas Pahlawan Tuanku Tambusai, 2022)
The success of a learning is in line with the selection of the curriculum to be used. The 2013 curriculum mandates the essence of a scientific approach in learning. In this case, it is necessary to develop attitudes, knowledge, and skills of students. The purpose of this study is to provide insight and an overview in designing and compiling a curriculum using a scientific approach to learning Arabic and providing examples of the application of this scientific approach to several schools that have implemented a curriculum with a scientific approach. The research method used is library research, where data collection methods are taken from various sources, namely from books, journals, and other sources that discuss the scientific approach in learning Arabic. The results of this study are the development of the syllabus, the development of a class-based testing system, the integration of life skills into the syllabus, and modifying the learning model. Teachers have been fully involved in developing the syllabus and learning. This can be seen from the ability of teachers in developing learning experiences into learning activities. So in this case, schools must complete the guidelines for implementing the 2013 curriculum. Guidance and training and monitoring of the implementation of the 2013 curriculum must be carried out continuously and sustainably.